Structural behavior of asphalt pavements / Lijun Sun - Sun, Lijun
This book provides engineers and researchers with a detailed guide to the structural behavioral dynamics of asphalt pavement including: pavement temperature distribution, mechanistic response of pavement structure under the application of heavy vehicles, distress mechanism of pavement, and pavement deterioration performance and dynamic equations.